KOMUNIKASI MEDIA MASSA DALAM PROMOSI WISATA BUDAYA DESA SADE PADA ERA NEW NORMAL - Memoriance Memoriance; Nyoman Murba Widana; Gusti Ayu Santi Patni (IAHN Gde Pudja Mataram, 2022)
The COVID-19 pandemic that has hit the world has made tourism now not run well, especially tourism in Sade Village, imperative Lombok. the brand new everyday technology is one of the opportunities inside the promoting of Sade Village tourism, the lack of information of the Sade community approximately the importance of generation is one of the declines inside the stage of tourist visits, however that is unique for Sade Village. This studies makes a speciality of 4 things, namely: Mass Media communication, Constraints, solutions from limitations, Implications. method The studies uses descriptive qualitative techniques, with the sort of facts series the usage of remark, interviews, and documentation. The data had been analyzed thru the ranges of reduction, publicity, and conclusion drawing so they come to be research consequences inside the shape of tips or pointers. The consequences of the studies display that the verbal exchange method executed went well in applying an knowledge of generation to the Sade Village supervisor regarding the usage of the internet site and the communique used, particularly verbal and non-verbal communique; the presence of miscommunication, budgetary constraints and human useful resource constraints; answers to troubles by being a good listener, preventing assuming with out previous affirmation and in search of as entire information as feasible, coordinating; the implications of mass media communique within the advertising of Sade Village tourism, particularly, Mass media implications for Sade Village tourism; mass media communication has an impact on the development of tourism in Lombok, mainly tourism in Sade Village; for those who eat mass media, it has an impact on new expertise and revel in about the village of Sade; Mass media communication has an effect on the mass media itself.